Enkripsi Citra Bitmap Menggunakan Algoritma Kompresi Lampel-Ziv-Welch (LZW) - Sudirman Sudirman (UIN Sumatera Utara, 2020)
The use of data in the form of image files has become more widespread in various fields. Therefore, security of image files from unauthorized persons is important. Various techniques to reduce file size, including securing files, have been developed, one of which is compression. Compression technique becomes important in processing large images such as Bitmap images. Ziv Welch seal is a loseless compression algorithm that can compress images without any loss of pixel elements in them or the resulting compression image is identical to the original image. The image will be encrypted first and then performed the compression technique using the Ziv Welch Lempel algorithm. The resulting compression is no longer in the form of images but in the form of files with the * .mat extension. The different file formats from images to non-image files can help avoid cryptanalysis